Effect of Noise Exposure on the Occupational Stress of Bus Drivers in Bojnourd, Iran in 2018 - Ahmad Alizadeh larimi; Jamshid Yazdani charati; Seyed Hojjat Mousavi Kordemiri; Sepideh kamali (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Noise is one of the most harmful physical issues in a workplace that can cause stress. Transit bus drivers are exposed to environmental and bus noises that can act as stressors for them. In this regard, the present study aimed to determine the effect of noise exposure on occupational stress of bus drivers in Bojnourd, Iran in 2018. Methods: This cross-sectional descriptive study was performed on 110 bus drivers in Bojnourd. The Philip L. Rice Questionnaire (1992) was used to assess their occupational stress, and SV 971 Sound Level Meter (SVANTEK-971) was used to measure noise exposure. Finally, the collected data were analyzed in SPSS software (version 20) using descriptive statistics (mean and standard deviation) and correlation statistical tests. Results: Based on the findings, the level of occupational stress was high, moderate, and low in 102 (92.7%), 4, and 4 cases, respectively. The results of the noise measurement revealed that the level of noise exposure was standard for all the subjects. The mean value of the equivalent continuous sound pressure level (LAeq) was 75.43±2.74 dB. There was no significant relationship between LAeq and the level of stress experienced by the drivers. However, there was a significant relationship between LAeq and the occupational interest subtest (P<0.01). Conclusion: Level of occupational stress was high in the studied bus drivers and noise exposure was lower than the threshold. Since statistical analysis did not indicate a significant relationship between occupational stress and noise exposure and the noise exposure level among drivers was low, this finding is considered acceptable.